Case Studies and Laboratory Testing Identification of Pathogenic Bacteria from the Digestive System in Chickens ( Salmonella sp. ) (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Salmonellosis is an infectious disease in humans and animals that caused by bacteria from the genus Salmonella. Salmonella is the causative agent salmonellosis which can cause diarrhea and systemic infections . Salmonellosis is one of the most common food-borne zoonotic diseases. common and economically important . This case study aims to identify Salmonella sp. obtained from chicken digestive samples sold at Alok Market, Sikka Regency. Sample collection came from sick chickens in the form of Cloaca Swabs . Samples were isolated on XLD ( Xylose Lysine Deoxycholate) media then incubated in 37°C milk for 24 hours . Furthermore, gram staining and biochemical tests were carried out in the form of catalase tests, TSIA tests, SIM tests, and SCA tests. Based on the results of laboratory tests with the techniques used were culture and isolation on XLD agar media, gram staining and biochemical tests on chicken feces samples showed positive results for Salmonella sp .